Penguatan Nilai Spiritualitas pada Anak Disabilitas Korban Pelecehan Seksual dalam Upaya Menghilangkan Rasa Trauma - Dicky Kurniawan; Fajar Utama Ritonga; Berlinati, Berlinati (Yayasan Literasi Sains Indonesia, 2024)
The objective of this community service project is to implement Islamic spiritual values in children with disabilities who are victims of sexual violence, using social work methods with the hope of healing the trauma they have experienced. The problem statement of this service project is the effectiveness of the therapy used to address the client's trauma. The Islamic spiritual therapy is conducted through the concept of tazkiyah al-nufus, which involves the stages of takhalli, tahalli, and tajalli. The method used in this service project is social work methodology, employing micro-level intervention and mini-project approaches. The intervention process involves stages of engagement, intake, assessment, planning, intervention, and evaluation over a period of three months, utilizing the Strength Quadrant to identify the strengths and weaknesses of the clients. The results of this service project indicate that the service program has provided positive changes for the clients, although it has not yet achieved maximum results. Clients have begun to show progress such as correctly pronouncing the Arabic alphabet and performing the five daily prayers. This service project offers a deep understanding of the benefits of Islamic spiritual therapy and social work methods in helping clients overcome trauma and psychological disorders, and provides recommendations for the development of future service programs. The innovation in this service project is the use of Islamic therapy combined with social work methods.